The effect of training and reward to employee performance at Terminal Bersepadu Selatan (TBS) / Rosli Jimat - Jimat, Rosli (2014)
This study is an attempt to address the relationship between Training, Reward and Employee Performance in organization. The researcher was use 85 respondents that different in their demographic background in Terminal Bersepadu Selatan (TBS). The respondents that took part in this study are among the non – executive staff. The researcher has chosen 70 respondents out of 85 for the results of findings that have been analyzed by using SPSS software. In this research, the researcher has use a questionnaire as the main data collection method. Pearson Correlation Coefficient test has been analyzed to reveal the result of direction and strength of correlation between the elements of both independent and dependent variables. The researcher has found the result that showed there is significant relationship between the training in the organization and employee performance, and also the relationship between reward in the organization and employee performance. The analysis also stated that the reward and training have a positive relationship with employee performance. However, Pearson Correlation Coefficient test was result that both of independent variables (Training and Reward) which is factor that affected employee performance in the organization. The researcher also has suggested some recommendations in order to improve the way of organization handling their training and reward in order to increase employee performance in their organization.